MOTOR VEHICLE TAXPAYER COMPLIANCE: AWARENESS, SOCIALIZATION AND MOTOR VEHICLE TAX AMOLISHMENT - Rahmadhani, Devi; Haryono (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2025)
This research aims to determine the influence of taxpayer awareness, tax socialization and motor vehicle tax relief on motor vehicle taxpayer compliance. The research method used is a quantitative research method. The object of this research is registered vehicle taxpayers registered at Samsat Serpong. The population of this study was 274,539 taxpayers, which was determined using the Slovin formula with an error rate α of 10%. The sample for this research consisted of 100 respondents, using the Accidental Sampling sampling technique. Data collection methods used were descriptive analysis validity test, reliability test, classic assumption test (normality test, multicollinearity test, heteroscedasticity test), autocorrelation test, multiple regression analysis, hypothesis testing (coefficient of determination test, F test, t test) with the help of SPSS software version 25. The results of this research show that Taxpayer Awareness, Tax Socialization and Motor Vehicle Tax Reduction simultaneously influence Motor Vehicle Taxpayer Compliance. Partially, the Motor Vehicle Taxpayer Awareness variable has an effect on Motor Vehicle Taxpayer Compliance, the Tax Socialization variable has no effect on Motor Vehicle Taxpayer Compliance, and the Motor Vehicle Tax Whitening variable has an effect on Motor Vehicle Taxpayer Compliance.